Off-target pesticide movement: a review of our current understanding of drift due to inversions and secondary movement - Bish, Mandy; Oseland, Eric; Bradley, Kevin (Weed technology, 2021)
Pesticide drift has been a concern since the introduction of pesticides. Historical incidences with off-target movement of 2,4-D and dichlorodiphenyltrichloroethane (DDT) have increased our understanding of pesticide fate in the atmosphere following aerial application. More recent incidences with dicamba have brought to light gaps in our current understanding of aerial pesticide movement following ground application. In this paper, we review the current understanding of inversions and other weather and environmental factors that contribute to secondary pesticide movement and raise questions that need to be addressed. Factors that influence volatility and terminology associated with the atmosphere, such as cool air drainage, temperature inversions, and radiation cooling will be discussed. We also present literature that highlights the need to consider the role(s) of wind in secondary drift in addition to the role in physical drift. With increased awareness of pesticide movement and more herbicide-resistant traits available than ever before, it has become even more essential that we understand secondary movement of pesticides, recognize our gaps in understanding, and advance from what is currently unknown. Nomenclature: dicamba; 2, 4-D; dichlorodiphenyltrichloroethane